Performance Standards for Restaurants A New Approach to Addressing the Obesity Epidemic - Cohen, Deborah (RAND Corporation, 2013)
This report presents the results of a conference of 38 national experts in nutrition and public health who met to develop performance standards that could guide restaurants toward facilitating healthier choices among consumers and that local communities or states could use as a model for developing and implementing either voluntary or mandatory certification programs.